PENCAPAIAN AKTUALISASI DIRI DALAM FILM DOKUMENTER - Nuraulia Muhibar (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2021)
The documentary film "Young Man and the Sea" (2012) is a documentary film that has a pattern of nostalgia recalled and developed to deliver a variety of messages about the idea of the director. This film studies using narrative analysis method which will discuss the story and associate it with the humanistic personality theory from the Abraham Maslow, the man as an individual has the freedom to choose an action, determine their own destiny or form from the existence and is responsible for all the options. Human needs are classified into six types, and the highest is Self-Actualization, namely the need to be someone who in accordance with the wishes and potentials of himself.